Analisis Semiotika Visual Pada Sampul Majalah Tempo Edisi “Noda Satu Putaran” - Damasemil, Calvin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2024)
The 2024 presidential election contest is deemed to have numerous violations and fraud. This has attracted the attention of the public and the mass media, especially Tempo Magazine. The magazine, known for its characteristic illustrated covers in every issue with various characters and visual styles that often become controversial, is the subject of this study. This research aims to uncover the meaning behind the cover of Tempo Magazine's February 18-25, 2024 edition titled